Aplikasi Sistem Informasi Geografis untuk Pemetaan Potensi Banjir pada DAS Banyualit di Kabupaten Banyuwangi, Jawa Timur - DICKY ARDIYAN NUGROHO PUTRA; WIYANTI WIYANTI; R. SUYARTO (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2022)
Geographical Information System Application for Flood Potention Mapping in Banyualit Watershed, Banyuwangi Regency, East Java The Banyualit Watershed has an area of 25 km2, through 5 sub-districts consisting of 15 villages from upstream to downstream. Banyualit watershed has varied physical conditions, causing the potential for scattered floods to have different levels. The use of space that is not accordance with the carrying capacity of the environment as a result of land conversion and changes in the morphology of the watershed are getting narrower causing the flow of water to overflow into residential areas, plantations and rice fields in the event of heavy rains with a high enough intensity. The purpose of this study was to determine the distribution of flood potential levels along with the spatial distribution of flood potential in Banyualit watershed. The method used in this study is a scoring with six parameters, land use, slope, altitude, soil type, rainfall and river density. Each parameter has weight and score based on the size of the effect on flooding. The level of distribution of flood potential in Banyualit watershed is divided into four classes of flood potential, very low potential with an area of 21.57 ha (1%), low potential with an area of 466.33 ha (19%), medium potential with an area of 1.812.41 ha (71%) and high potential with an area of 224.44 ha (9%).